Assessment of genetically modified maize MON 87403 for food and feed uses, import and processing, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐BE‐2015‐125). (28th March 2018) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: Maize MON 87403 was developed to increase ear biomass at early reproductive phase through the expression of a modified AtHB17 gene from Arabidopsis thaliana, encoding a plant transcription factor of the HD‐Zip II family. The molecular characterisation data and bioinformatic analyses did not identify issues requiring assessment for food and feed safety. No statistically significant differences in the agronomic and phenotypic characteristics tested between maize MON 87403 and its conventional counterpart were identified. The compositional analysis of maize MON 87403 did not identify differences that require further assessment. The GMO Panel did not identify safety concerns regarding the toxicity and allergenicity of the AtHB17∆113 protein, as expressed in maize MON 87403. The nutritional value of food and feed derived from maize MON 87403 is not expected to differ from that of food and feed derived from non‐genetically modified (GM) maize varieties. Based on the outcome of the studies considered in the comparative analysis and molecular characterisation, the GMO Panel concludes that maize MON 87403 is as safe and nutritious as the conventional counterpart and the non‐GM maize reference varieties tested. In the case of accidental release of viable maize MON 87403 grains into the environment, maize MON 87403 would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of maize MON 87403. In conclusion, the GMO Panel considers that maize MON 87403, as described in this application, is as safe as its conventional counterpart and the tested non‐GM maize reference varieties with respect to potential effects on human and animal health and the environment.